Analysis of physical training influence on the technical execution of the dismounts off the uneven bars - Potop, V.; Cretu, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2018)
Purpose: highlighting of physical training dynamics and its influence on the biomechanical characteristics of the dismounts off uneven bars executed by junior gymnasts aged 12 to 15 years.